Mutual fund performance evaluation: an empirical investigation of Greek mutual fund performance evaluation using Morningstar’s methodology - Φίλιππας Νικόλαος Δ.; Νικολαΐδου Έλενα (SPOUDAI Journal of Economics and Business, 2005)
In this article Greek Equity Mutual Funds are evaluated for the first time using the Morningstar methodology. In addition, for comparability reasons, we present results using Jensen's methodology. The two methods do not rank the Mutual Funds under examination accordingly, however, using the Spearman criterion, the correlation coefficient was found to be statistically significant at 0,42. Finally, we tested the consistency of performance of mutual fund managers through time. The empirical results show that past rankings of mutual funds can be used to predict future rankings, a finding that contradicts the theory of market efficiency. JEL Classifications: G20, G23, G29